2014
DOI: 10.1128/jcm.02485-13
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens of Bovine Respiratory Disease in North American Feedlots Conferring Multidrug Resistance via Integrative Conjugative Elements

Abstract: In this study, we determined the prevalence of bovine respiratory disease (BRD)-associated viral and bacterial pathogens in cattle and characterized the genetic profiles, antimicrobial susceptibilities, and nature of antimicrobial resistance determinants in collected bacteria. Nasopharyngeal swab and lung tissue samples from 68 BRD mortalities in Alberta, Canada (n ‫؍‬ 42), Texas (n ‫؍‬ 6), and Nebraska (n ‫؍‬ 20) were screened using PCR for bovine viral diarrhea virus (BVDV), bovine respiratory syncytial viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
176
1
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(200 citation statements)
references
References 42 publications
10
176
1
13
Order By: Relevance
“…They found a prevalence of P. multocida from 7.11% to 14.09% in the states of Hidalgo and Queretaro, as well as a prevalence of M. haemolytica of 28.03%, which might have been caused by the use of bacterial culture as a diagnostic technique. PCR, on the other hand, is a more sensitive test that allowed the detection of a number of cases that failed to be detected by culture (6). Studies carried out in Colima and Yucatán found the BRSV average seroprevalences to be 50.8% and 90.8%, respectively (14,15), which are similar to the results found in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…They found a prevalence of P. multocida from 7.11% to 14.09% in the states of Hidalgo and Queretaro, as well as a prevalence of M. haemolytica of 28.03%, which might have been caused by the use of bacterial culture as a diagnostic technique. PCR, on the other hand, is a more sensitive test that allowed the detection of a number of cases that failed to be detected by culture (6). Studies carried out in Colima and Yucatán found the BRSV average seroprevalences to be 50.8% and 90.8%, respectively (14,15), which are similar to the results found in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Although clinical signs may raise the suspicion of BRD infection, laboratory confirmation is needed to make a definitive diagnosis. BRD diagnosis can be achieved by a variety of serological methods, agent isolation, fluorescent antibodies tests, immunohistochemistry, and molecularbased tests (6). Irrespective of the infectious agent involved, the presenting clinical signs of BRD can appear similar.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria most frequently associated with BRD are Mannheimia haemolytica, Pasteurella multocida, Histophilus somnus, Mycoplasma bovis, and occasionally Trueperella pyogenes (Griffin et al, 2010;Klima et al, 2014). Strains of these bacteria are considered opportunistic pathogens and are isolated from both healthy and sick cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers sampled the upper airways of live animals (Corstvet et al, 1973), bronchoalveolar lavages (Caldow, 2001 and Senthilkumaran et al, 2013) while most studies have sampled lungs from animals that succumbed to BRD (Martin, 1983;Fulton et al, 2009;Burgess et al, 2011;and Klima et al, 2013). However, despite the likely importance of the nasal cavity as an Prior to this investigation, there have been no studies to characterise the biochemical and immunological properties of bovine NS.…”
Section: Discussionmentioning
confidence: 99%